A ¼ scale hybrid full-tracked air-cushion vehicle for swamp peat terrain in Malaysia - Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Hossain, Altab; Nursyifa, S.; Nora, A.; Hidayah, N.; Eshah, J. (2007)
This paper describes design and development of a hybrid full rubber track air-cushion vehicle (HTACV) for collection-transportation operation of palm oil fresh fruit bunches (FFB) on the low bearing capacity of 7 kN/m2 swamp peat terrain. The full segmented rubber track mechanism is used as the driving system to overcome the rolling motion resistance and the air cushion system is used to increase the floatation capacity of the vehicle. The driving force is provided to each of the track system by an individual AC motor. The additional thrust (or ,tractive effort) is provided to the vehicle by using two propulsion systems for overcoming the drag resistance of the air-cushion system. Mathematical models are incorporated by accounting the kinematics and dynamics behavior of the vehicle. The simulation of the tractive performance has been found as 65% traction coefficient and 80% tractive efficiency.